Characterizing and correcting immune dysfunction in non-tuberculous mycobacterial disease - Ratnatunga, Champa N.; Tungatt, Katie; Proietti, Carla; Halstrom, Sam; Holt, Michael R.; Lutzky, Viviana P.; Price, Patricia; Doolan, Denise L.; Bell, Scott C.; Field, Matt A.; Kupz, Andreas; Thomson, Rachel M.; et al. (Frontiers in Immunology, 2022)
Non-tuberculous mycobacterial pulmonary disease (NTM-PD) is a chronic, progressive, and growing worldwide health burden associated with mounting morbidity, mortality, and economic costs. Improvements in NTM-PD management are urgently needed, which requires a better understanding of fundamental immunopathology. Here, we examine temporal dynamics of the immune compartment during NTM-PD caused by Mycobacterium avium complex (MAC) and Mycobactereoides abscessus complex (MABS). We show that active MAC infection is characterized by elevated T cell immunoglobulin and mucin-domain containing-3 expression across multiple T cell subsets. In contrast, active MABS infection was characterized by increased expression of cytotoxic T-lymphocyte-associated protein 4. Patients who failed therapy closely mirrored the healthy individual immune phenotype, with circulating immune network appearing to ‘ignore’ infection in the lung. Interestingly, immune biosignatures were identified that could inform disease stage and infecting species with high accuracy. Additionally, programmed cell death protein 1 blockade rescued antigen-specific IFN-γ secretion in all disease stages except persistent infection, suggesting the potential to redeploy checkpoint blockade inhibitors for NTM-PD. Collectively, our results provide new insight into species-specific ‘immune chatter’ occurring during NTM-PD and provide new targets, processes and pathways for diagnostics, prognostics, and treatments needed for this emerging and difficult to treat disease